Prevalence and antibiotic resistance of bacterial pathogens isolated from childhood diarrhoea in four provinces of Kenya - Willie Kipkemboi Sang; Valerie Oundo; David Schnabel (Journal of Infection in Developing Countries)
Introduction: Diarrhoea is one of the main causes of morbidity and mortality among children in sub-Saharan Africa, and one of the main causes of hospital admissions in rural areas of Kenya. In Kenya, antimicrobial resistance surveillance has been conducted only at the institutional levels, with limited sharing of information and analysis of data. As a result, the actual scale of regional or national antimicrobial drug resistance is not well defined.